2011
DOI: 10.1007/s11011-011-9261-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver induces insulin resistance and metabolic disorders with development of brain damage and dysfunction

Abstract: In the present study we investigated the effect of the non-alcoholic fatty liver disease (NAFLD) on the alterations in the activity of neurotransmitters catabolizing enzymes and energy catabolising enzymes, prooxidants, endogenous antioxidants and proinflammatory cytokines in brain tissue of NAFLD rats. Rats were intraperitonealy injected with CCl4 solution at a dose of (0.021 mole/Kg, 20 μL, body weight) three times weekly for four weeks. Acetylcholine esterase (AChE), monoamine oxidase (MAO), prooxidant/ ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 86 publications
1
40
0
Order By: Relevance
“…These findings fit with prior evidence indicating that higher insulin levels co-exist with elevated levels of TC and TG in the progressive state of NAFLD [35], as well as studies showing that suppression of very-low-density lipoprotein secretion and fatty acid β-oxidation produces hepatic TG accumulation [5,6]. Although body weight change did not differ among the groups in our study, we did observe a significant increase in relative liver weight and hepatic steatosis accompanied by a partial mild inflammationin the HF group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings fit with prior evidence indicating that higher insulin levels co-exist with elevated levels of TC and TG in the progressive state of NAFLD [35], as well as studies showing that suppression of very-low-density lipoprotein secretion and fatty acid β-oxidation produces hepatic TG accumulation [5,6]. Although body weight change did not differ among the groups in our study, we did observe a significant increase in relative liver weight and hepatic steatosis accompanied by a partial mild inflammationin the HF group.…”
Section: Discussionsupporting
confidence: 91%
“…Although no significant effects of dietary BRE supplementation on insulin resistance were observed in our model, the reduced serum TG and TC levels observed in the HF + BRE1% group were associated with a reduction in hepatic steatosis relative to that seen in the HF group [35]. BRE supplementation was also associated with fewer visible steatotic livers compared with that in mice fed a high-fat diet without BRE supplementation.…”
Section: Discussionmentioning
confidence: 73%
“…Diet-induced insulin resistance also accelerated Aβ pathology by activating γ-secretase and inactivating insulin-degrading enzyme in the Tg2576 AD mouse model [42]. Furthermore, insulin resistance-mediated activation of neurotransmitter catabolizing enzymes, including acetylcholine esterase and monoamine oxidase, was suggested to act as a relative risk factor for brain dysfunction and damage in rats with nonalcoholic fatty liver disease [44]. ER stress has been shown to play an important role in tau phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is the hepatic manifestation of MetS and is considered an independent risk factor for CVD. Ghareeb et al (2011) have demonstrated that NAFLD may induce insulin resistance and metabolic disorders associated with age-associated neurodegenerative diseases such as AD.…”
Section: Iron Metabolismmentioning
confidence: 99%